Portions of the Book of common prayer, hymns, etc., in the Chipewyan language [electronic resource] - Church of England.; Kirkby, W. W. (William West), 1827-1907.; Bompas, William Carpenter, 1834-1906. (London : Society for Promoting Christian Knowledge)
Text in Roman characters. Electronic reproduction. Mode of access: Internet. 44